Universitários de educação física são otimistas e motivados durante a vida acadêmica? - Borsato Passos, Patricia Carolina; Arantes da Costa, Luciane Cristina; Contreira, Andressa; Belem, Isabella; Silva, Eraldo da; Fiorese, Lenamar (2020)
The objective is to analyze the life orientation and the academic motivation of university students of the Physical Education course of study during the four years of initial training. Twenty-four undergraduate students of the full-time Physical Education course from a public university in southern Brazil participated in this longitudinal study. As research instruments, the Life Orientation Test (TOV-R), the Academic Motivation Scale and an identification questionnaire were used. The Friedman test, the Mann-Whitney U test, the Kruskal-Wallis test and the Spearman correlation (p <0.05) were used for the statistical analysis. The results show that the level of optimism did not change over the years, although the levels of motivation showed significant differences among the years. The results of the correlation showed that the fewer hours of physical exercise performed by the students, the more unmotivated they were (p=0.04) and the higher the age group, the higher the levels of intrinsic motivation (r=0.60). We conclude that Physical Education students are optimistic throughout initial training. However, it was verified that during the first year of training academics are more unmotivated than during other years.
Objetivo: Analisar a orientação de vida e a motivação acadêmica de universitários do curso de Educação Física ao longo dos quatro anos de formação inicial. Métodos: Participaram deste estudo de cunho descritivo longitudinal 24 universitários do curso de Educação Física do período integral, estudantes de uma universidade pública do sul do Brasil. Como instrumentos de pesquisa foram utilizados o Teste de orientação de vida (TOV-R), a Escala de Motivação Acadêmica e um questionário de identificação. Utilizou-se para análise estatística o teste de Friedman, o teste de U de Mann-Whitney, o Kruskal-Wallis e correlação de Spearman (p<0,05). Resultados: O nível de otimismo não se alterou ao longo dos anos, já os níveis de motivação apresentaram diferenças significativas entre os anos. Os resultados da correlação demonstraram que quanto menos horas de prática de exercício físico realizada pelos os acadêmicos, mais desmotivados eles se percebem (p= 0,04) assim como que quanto maior a faixa etária maiores níveis de motivação intrínseca (r= 0,60). Conclusão: Os universitários de Educação Física são otimistas durante toda a formação inicial. Ainda, constatou-se que no primeiro ano os acadêmicos são mais desmotivados quando comparados aos outros anos da formação.
Keywords: University; Motivation; Optimism; Students; Universitário^lpt; Motivação; Otimismo; Acadêmicos